DYNAMICS OF NON-PESANTREN EDUCATION AT AL-HAMIDIYAH SEI SIONGGOTON PONDOK, KECAMATAN SIMANGAMBAT, PADANG LAWAS UTARA DISTRICT - Abbas Siregar (Proceeding International Seminar of Islamic Studies, 2021)
This is in accordance with the objectives of National education in Indonesia. In general, education in Islamic boarding schools is dominated by religious education but still studies general education as regulated in the Decree of three Ministers on Education. With qualitative research methods it was found that: 1). Pondok Pesantren Al-Hamidiyah in the third year since its establishment until now, it has opened extracurricular classes starting from farming by bringing students to work on the agricultural fields of the Pesantren leadership, building engineering, sewing courses to mechanic classes for motorbike and welding workshops. 2). The purpose of opening non-pesantren extracurricular classes is to increase the interest of the community to send their children to the Al-Hamidiyah Islamic boarding school. 3). The advantage of non-pesantren extracurricular classes is that they are able to change the thinking of the surrounding community from previously thinking that Islamic boarding schools only produce ulama candidates, but now Al-Hamidiyah Islamic Boarding School is also able to produce graduates who have general skills while still having religious knowledge. 4). The weakness is that it affects Islamic boarding schools extracurricular activities such as Pidato, Tahfiz, Kalighrafi and others.Keywords: Non-Islamic Boarding School Education, Extracurricular, Pesantren Dynamics